Strategies for poverty alleviation and sustainable resource management in the fragile lands of Sub-Saharan Africa - Knox, Anna; Babu, Suresh Chandra; Hazell, Peter B. R. (Deutsche Stiftung für internationale Entwicklung, 1999)
Partial contents: Workshop summary / Anna Knox McCulloch [IFPRI staff], Suresh Babu [IFPRI staff], Tidiane Ngaido [IFPRI staff] -- Growth, poverty alleviation, and the environment in the fragile lands of Sub-Saharan Africa / Suresh Babu and Peter Hazell [IFPRI staff] -- Spatial aspects of the design and targeting of development strategies for fragile lands / Stanley Wood [IFPRI staff] ... [et al.] -- The impact of policy reforms and trade liberalization on fragile lands in Sub-Saharan Africa / Awudu Abdulai and Peter Hazell -- Strategies for sustainable agricultural development in the East African highlands / John Pender [IFPRI staff] ... [et al.] -- Property rights institutions for the development of fragile lands / Anna Knox McCulloch and Peter Hazell -- Dambo Irrigation systems: indigenous water management for food security in Zimbabwe / Ruth Meinzen-Dick [IFPRI staff] and Godswill Makombe.